The Mechanisms of Applying Open Book ‎Management Approach at Shaqra University ‎in the Kingdom of Saudi Arabia - Al-Saab, Manal (Jordan Journal of Educational Sciences, 2023)
The study aimed to identify the reality of applying the open-book management approach at Shaqra University, determine whether there are statistically significant differences for variables (gender-type of work); and define the difficulties of applying the open-book management approach at Shaqra University to develop proposed mechanisms for applying the open-book management approach based on the results of the study. The researcher used the descriptive survey approach and the questionnaire as the tool for data collection. The study population included the college’s deans and deputies of the university who are (51). The study mainly revealed the following results: the reality of applying the open-book management approach at Shaqra University is moderate as follows (education and training - organizational environment - support and motivation), and there are no statistically significant differences in the gender and type of work.. The most prominent difficulties limiting the application of the open-book management approach at Shaqra University are: bureaucracy in work performance and the ambiguity of the criteria for nominating leadership selection. In addition, the study concluded with the development of the most important measures that help to apply the open-book management approach at Shaqra University, including creating a favorable environment for spreading out the open-book management approach and empowering employees by delegating greater powers to the middle and lower levels according to the abilities and skills of workers